ANALYSIS OF RAINFALL AND TEMPERATURE CHANGES IN GOMBE STATE, NIGERIA - Bello, Yusuf; Adebayo, Aderemi Able; Abubakar, Bashir (FUDMA Journal of Sciences, 2020)
This study analyses the rainfall and temperature trends of three (3) Agro-Ecological zones of Gombe State. The data for this study were sourced from the Nigerian Meteorological Agency (NiMet), Gombe State Agricultural Development Program (GSADP), and Upper Benue River Basin Development Authority (UBRBDA). The data were subjected to Linear Time Series Analysis, Mann-Kendall Z- Statistics, Sen’s Slope Estimator and Linear Growth Model. The results revealed an increasing pattern of temperature in all the zone. The mean temperature for the study period revealed an increasing rate of 0.0352oC, 0.0031oC and 0.0281oC in the Southern Guinea Savannah (SGS), Northern Guinea Savannah (NGS) and Sudan Savanna (SS) respectively. The annual rainfall revealed a decreasing trend at the rate -0.957mm, -2.74mm and -0.87mm per-1in SGS, NGS and SS respectively while Gombe station in NGS revealed an increasing trend at the rate of 3.05mm per-1. The projected trends revealed that there is going to be decreasing of temperature for Billiri station in SGS and an increasing trend of rainfall for Gombe station in NGS for the coming decades. The study concludes that there is a significant increase of temperature in all the zones and there is no statistical trend of rainfall in SS. The current trend will affect soil moisture, crop water requirement and subsequently lead to ecological change. The study recommends that inhabitants of the study areas should plan their cropping season based on climatic information of their area.